(untitled) (European Journal of Pure and Applied Mathematics, 2025)
This study examines the oscillatory performance of solutions of functional differential equations with an advanced argument. Equations of the advanced type have not received as much study as equations with delay. We deduce some new monotonic properties of the positive solutions of the studied equation. Then, we use these properties to obtain criteria that test the oscillatory nature of the solutions. We apply the results to some special cases, compare them with previous results, and analyze the results to demonstrate the novelty and importance.